The influence of therapeutic horticulture on social integration. Issue 3 (19th September 2016) - Howarth, Michelle Louise; McQuarrie, Cath; Withnell, Neil; Smith, Emma
Abstract : Purpose: The purpose of this paper is to qualitatively evaluate the impact of therapeutic horticulture (TH) on social integration for people who have mental health problems. Design/methodology/approach: A qualitative grounded theory approach captured the perceptions about TH from people with mental health problems. Data were collected using semi-structured focus group and interviews from a purposive sample ( n =7) and were analysed using a constant comparative approach. Findings: Four key themes emerged from the analysis: "a space to grow", "seeing the person", "learning about each other through nature" and "connecting to nature and others". The findings suggest that TH enabled participants to integrate socially, engage with nature and develop confidence. Research limitations/implications: TH is a potential approach that can help combat social isolation. The findings from this research have implications for people working towards supporting people who are socially excluded. However, this was a pilot study with a small sample size of seven people with mental health problems, whilst four key themes emerged, the saturation of concepts rather than the sample size were saturated to provide an emic perspective of the phenomena. Practical implications: TH provides a person centred approach that enables people with mental health problems to re-engage and connect with their fellow human beings. Using TH could help improve the public health and well-being of local communities through re-connecting people to the environment and reduce social isolation. Social implications: TH embody the principles of empowerment, person centeredness and can support people with mental health problems to integrate socially. Originality/value: There is limited evidence about the influence that TH have on mental health and social integration. The use of TH is an area that is gathering evidence and this small study highlights the perceived potential benefits of this approach.